Relevancy of foreign employment in the present context of Nepal - Joshi, Uttam Lal (International Research Journal of MMC, 2020)
There is more charm on foreign employment since decades. Due to lack of employment opportunities in public and private sectors, Nepali people are motivated to go foreign countries for job opportunities. Handsome salaries, respected life, relief from poverty and fulfillment of needs – these are the common motivators that lead people for foreign employment. This can be right in one aspect but there are a lot of evidences and scenarios that show foreign employment is not so easier and fruitful as it is thought. Foreign employees have to face many more difficulties and obstacles in foreign countries that one will explain after his return to home country. So the income from their hard labor must be utilized in proper sectors. Various data in this study show the foreign employment is not so safe. Here, the time series data from 2002/03 to 2019 are taken for the study of the relationship between remittance and investment. The regression analysis with P-value 0.000 at 5% significant level (α= 0.05) which shows that the remittance from foreign employment has been used in investment anyway. It will help to find the productivity, relevance and proper use of the income from foreign employment.